Cold-induced hepatocyte-derived exosomes activate brown adipose thermogenesis via miR-293-5p-mediated transcriptional reprogramming - Xiujuan Gao; Junqing Xu; Zengqiang Xu; Mengxin Jiang; Jiahao Zhu; Yang Geng; Shengjun Dong; Yanuo Li; Zhengtong Zhou; Yingjiang Xu (Cell Death Discovery)
Abstract The liver-adipose axis represents a crucial regulatory network that governs systemic lipid homeostasis, with signals originating from the liver orchestrating the plasticity of adipose tissue through diverse mechanisms. A comprehensive understanding of these bidirectional communication pathways may uncover novel therapeutic approaches for metabolic disorders. Our research demonstrates that exposure to cold stimulates the liver to secrete exosomes, which enhance thermogenic activation in adipose tissue, as observed in both in vitro and in vivo models. This enhancement of thermogenesis is mechanistically associated with the cold-induced upregulation of hepatocyte-derived exosomal miR-293-5p. Importantly, the pharmacological administration of a miR-293-5p agomir significantly mitigates diet-induced obesity and related metabolic dysfunctions in murine models. Through mechanistic analysis, we identified Tet1 as a direct downstream target of miR-293-5p, noting that the ectopic expression of Tet1 disrupts the thermogenic programming of brown adipose tissue (BAT) independently of miR-293-5p modulation. Our findings establish cold-activated hepatocyte exosomes as endocrine signaling mediators that carry thermogenic microRNA cargos, with miR-293-5p emerging as a key regulator.